2018
DOI: 10.1038/s41467-018-07139-4
|View full text |Cite
|
Sign up to set email alerts
|

Pressure shock fronts formed by ultra-fast shear cracks in viscoelastic materials

Abstract: Spontaneously propagating cracks in solids emit both pressure and shear waves. When a shear crack propagates faster than the shear wave speed of the material, the coalescence of the shear wavelets emitted by the near-crack-tip region forms a shock front that significantly concentrates particle motion. Such a shock front should not be possible for pressure waves, because cracks should not be able to exceed the pressure wave speed in isotropic linear-elastic solids. In this study, we present full-field experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
63
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(69 citation statements)
references
References 54 publications
2
63
1
Order By: Relevance
“…In a recent study [76], we have observed the formation of pressure shock fronts associated with the spontaneous propagation of shear ruptures in viscoelastic polymers, apparently contradicting classic linear elasticity theory. This contradiction is explained with the high-strain-rate dependence of the polymers inducing local stiffening of the material and locally increasing the effective wave speeds as the crack tip is approached, resulting in the rupture tip propagating slightly less than, or equal to, the local, near-tip pressure wave speed but above the wave speed prevailing in far-field, thus giving rise to the formation of a pressure shock front, in addition to a trailing shear Mach Cone [76]. In other words, the wave speeds, instead of having a single value as in linear elasticity, depending on the local value of the strain rate field at each point, and as such, they exhibit a field variation themselves.…”
Section: Imaging the Formation Of Pressure Shock Frontscontrasting
confidence: 65%
See 4 more Smart Citations
“…In a recent study [76], we have observed the formation of pressure shock fronts associated with the spontaneous propagation of shear ruptures in viscoelastic polymers, apparently contradicting classic linear elasticity theory. This contradiction is explained with the high-strain-rate dependence of the polymers inducing local stiffening of the material and locally increasing the effective wave speeds as the crack tip is approached, resulting in the rupture tip propagating slightly less than, or equal to, the local, near-tip pressure wave speed but above the wave speed prevailing in far-field, thus giving rise to the formation of a pressure shock front, in addition to a trailing shear Mach Cone [76]. In other words, the wave speeds, instead of having a single value as in linear elasticity, depending on the local value of the strain rate field at each point, and as such, they exhibit a field variation themselves.…”
Section: Imaging the Formation Of Pressure Shock Frontscontrasting
confidence: 65%
“…In order to confirmed that the shock fronts visualized are indeed Mach features, rather than some other manifestation of the corresponding waves, we have verified that the characteristic geometric feature of such fronts (i.e., inclination angle β with respect to the interface) satisfies the kinematic relation characteristic of Mach waves [76]: β = sin −1 (c/V r ), where V r is the measured rupture speed and c is either the pressure or shear wave speed (depending on the front considered). We have explained this behavior by the viscoelastic effects of the polymers resulting in a significant increase in the elastic moduli and effective wave speed with strain rates [76]. The high degree of variability of elastic moduli with strain rates is extensively documented in the literature [145][146][147][148][149].…”
Section: Imaging the Formation Of Pressure Shock Frontsmentioning
confidence: 63%
See 3 more Smart Citations